1997
DOI: 10.1051/alr:1997038
|View full text |Cite
|
Sign up to set email alerts
|

Light intensity affects growth and sexual maturation of Atlantic salmon (Salmo salar) postsmolts in sea cages

Abstract: The aim of thc prcscnt study is to test the extent to which dil'ferent interisities of continuous additional light affcct somatic growth and scxual maturation in Atlantic salmon postsmolts in sea cages. Postsmolts (Y 200 individuals) were randomly distributed among four cornmcrcial sizcd sca cages and exposed to either natural light or natural light + continuous additional liglit of low, medium or high intensity from January to Junc. In May the high light intensity group had a signitïcantly higher mean live bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 19 publications
(31 reference statements)
10
70
1
2
Order By: Relevance
“…The delayed increase in body mass observed in the continuous light treatment probably reflects the time required for hypertrophy of the muscle fibres produced once the inhibitory effects of short day length are removed. A similar delay in the growth-stimulating effects of continuous light treatment has been observed previously (Oppedal et al, 1997). It has been suggested that the ratio between day/night light intensity is important with respect to the timing and increase in growth rate observed (Steffansson et al, 1991).…”
Section: A Johnston and Otherssupporting
confidence: 80%
See 1 more Smart Citation
“…The delayed increase in body mass observed in the continuous light treatment probably reflects the time required for hypertrophy of the muscle fibres produced once the inhibitory effects of short day length are removed. A similar delay in the growth-stimulating effects of continuous light treatment has been observed previously (Oppedal et al, 1997). It has been suggested that the ratio between day/night light intensity is important with respect to the timing and increase in growth rate observed (Steffansson et al, 1991).…”
Section: A Johnston and Otherssupporting
confidence: 80%
“…Endal et al (2000) also reported that holding fish on long days from November to July failed to reduce maturity; indeed, in their study maturity was significantly enhanced. The relationships between the light intensity of the extended photoperiod, growth rate and maturity may be more complex than previously considered (Oppedal et al, 1997).…”
Section: A Johnston and Othersmentioning
confidence: 97%
“…Our results showed a significant growth enhancing effect of exposure to 24L:0D and 18L:6D regimes in rainbow trout, Oncorhynchus mykiss. The data obtained from this experiment is consistent with that from other experiments on juvenile and adult salmons (Endal et al, 2000;Oppedal et al, 1997;Porter et al, 1999;Sigholt et al, 1997;Taranger et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Continuous additional light has also been used on the Atlantic salmon reared in the sea cages, especially during the spring and winter to enhance growth and delay sexual maturation rate (Taranger et al, 1995;Oppedal et al, 1997;Porter et al, 1999). Photoperiod manipulation applied in fish farming intends to increase the farming efficiency and get the fish to the commercial weight as soon as possible .…”
Section: Introductionmentioning
confidence: 99%
“…Resultados semelhantes a este em que os pesquisadores verificaram uma relação positiva entre exposição à luz contínua crescimento somático e ingestão alimentar. Esta relação foi observada em salmão do Atlântico (OPPEDAL et al, 1997) em bacalhau do Atlântico, Gadus morhua (HANSEN et al, 2001;TARANGER et al, 2006), em Melanogrammusa eglefinus (DAVIE et al, 2007) e Pagrus major (BISWAS et al, 2010) e Sparus aurata (GINÉS et al, 2004).…”
Section: Resultsunclassified